Study on Epoxy-Phosphate Conversion Coating - Quan Hu, Yi Zhang, Gang Liu, Taishan Hu, Shangmao Hu, Li Bo (Forest Chemicals Review, 1970)
E44 epoxy resin was reacted with phosphoric acid to prepare epoxy-phosphate conversion coating. The coating was applied on the surface of rusty Q235 steel to form rust conversion coating. The effect of rust conversion coating was evaluated by photo recording, scanning electron microscopy and energy dispersive spectrometry. The performance of rust conversion coating was characterized by adhesion test and salt spray test. The results show that the coating with the molar ratio of E44 / phosphoric acid of 1:3 has the best adhesion, 3.4 MPa; the coating with the molar ratio of E44 / phosphoric acid of 1:2 has the longest salt spray test time, 500 h.